2014
DOI: 10.1021/jp506150r
|View full text |Cite
|
Sign up to set email alerts
|

Tautomerism in Porphycenes: Analysis of Rate-Affecting Factors

Abstract: Double hydrogen transfer occurring in both ground and the lowest electronically excited singlet states was studied for a series of 19 differently substituted porphycenes. The rates of tautomerization have been determined using femtosecond pump-probe spectroscopy with polarized light. The values vary by over 3 orders of magnitude, suggesting the importance of tunneling. Good correlation exists between the values of the rates and the parameters characterizing the strength of two intramolecular hydrogen bonds: pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 69 publications
3
37
0
Order By: Relevance
“…Satisfactory fits were observed for ν˜0 varying between 2300 and 2600 cm −1 and d 0 around 250 pm. We note that these values are close to those postulated for porphycenes, which form exceptionally strong intramolecular H‐bonds …”
Section: Resultssupporting
confidence: 87%
“…Satisfactory fits were observed for ν˜0 varying between 2300 and 2600 cm −1 and d 0 around 250 pm. We note that these values are close to those postulated for porphycenes, which form exceptionally strong intramolecular H‐bonds …”
Section: Resultssupporting
confidence: 87%
“…Experiments on symmetric medium and strong H-bonded systems are desirable. Some possible candidates are carboxylic acid dimers (R 2.45Å), HCrO 2 (R 2.49Å), porphycenes 51 , and proton sponges 52 , for which the fundamental, first overtone, and isotope effect could be measured and analysed. Slightly asymmetric biomolecular systems with strong H-bonds that could be investigated include mutated GFP 53 , photoactive yellow protein 54 and the enzyme KSI 55 .…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…It has also been found that the reaction barrier is essentially associated with the hydrogen bond strength (geometry) of the N-H···N moiety in the molecular cavity 39 . The increased barrier for the adsorbed porphycene on Cu(110) could be attributed to the change in the hydrogen bond through the formation of a dative bond of the lone pair orbitals of the imine N atoms with the surface Cu atoms.…”
mentioning
confidence: 99%